Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1073/pnas.2205425119
|View full text |Cite
|
Sign up to set email alerts
|

A partnership between the lipid scramblase XK and the lipid transfer protein VPS13A at the plasma membrane

Abstract: Chorea-acanthocytosis (ChAc) and McLeod syndrome are diseases with shared clinical manifestations caused by mutations in VPS13A and XK, respectively. Key features of these conditions are the degeneration of caudate neurons and the presence of abnormally shaped erythrocytes. XK belongs to a family of plasma membrane (PM) lipid scramblases whose action results in exposure of PtdSer at the cell surface. VPS13A is an endoplasmic reticulum (ER)-anchored lipid transfer protein with a putative role in the transport o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 70 publications
(115 reference statements)
4
48
0
Order By: Relevance
“…Thus, ColabFold predicts that the rod-like molecule VPS13 forms a single continuous β-groove from end to end, resembling other members of the superfamily (Figure 2D). This matches cryo-EM observations of VPS13 as a rod (De et al, 2017) with a groove along at least part of its length (Li et al, 2020), and has been reported elsewhere (Adlakha et al, 2022; Guillén-Samander et al, 2022). This finding indicates that the VAB repeats, six all-beta domains of a unique type that build into a curved structure shaped like a hook (Bean et al, 2018; Adlakha et al, 2022), can be considered as a VPS13-specific insert in the loop between RBG domains (RBG10 and 11, see Figure 1A).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, ColabFold predicts that the rod-like molecule VPS13 forms a single continuous β-groove from end to end, resembling other members of the superfamily (Figure 2D). This matches cryo-EM observations of VPS13 as a rod (De et al, 2017) with a groove along at least part of its length (Li et al, 2020), and has been reported elsewhere (Adlakha et al, 2022; Guillén-Samander et al, 2022). This finding indicates that the VAB repeats, six all-beta domains of a unique type that build into a curved structure shaped like a hook (Bean et al, 2018; Adlakha et al, 2022), can be considered as a VPS13-specific insert in the loop between RBG domains (RBG10 and 11, see Figure 1A).…”
Section: Resultssupporting
confidence: 90%
“…Analysis of the predicted structures of these proteins identified a repeating unit consisting of a 5-stranded β-sheet meander plus a sixth element, which usually starts with a helix and then continues with a loop that crosses back over the meander (Figure 1B) (Neuman et al, 2022b). The rods are superhelical, which makes it hard to see the details of their construction (Guillén-Samander et al, 2022; Toulmay et al, 2022). There are some portions of predicted structure where the superhelical twist is low, and here the core building block is easily seen (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it remains to be analyzed whether Vps13 binds to a dedicated scramblase or relies directly or indirectly on Atg9-mediated scrambling within the phagophore membrane. Recent work has identified that yeast Vps13 and human VPS13A are coupled with the scramblases Mcp1 in mitochondria and XK in the plasma membrane, respectively (Adlakha et al, 2022; Guillen-Samander et al, 2022; Park et al, 2022). Human VPS13A-D variants are associated with distinct pathologies (Ugur et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Atg2, proposed to transfer bulk lipids from the ER during autophagosome biogenesis, interacts with two ER-resident scramblases TMEM41B 52,53 and VMP1 53 , and with a Golgi-resident scramblase Atg9, that initiate the foramtion of autophagosome 51 . Vps13A was suggested to interact with a PM-resident scramblase XK [54][55][56][57] . It is tempting to speculate that SHIP164 may also cooperate with scramblases to mediate the lipid transfer from the Golgi to EEs.…”
Section: Discussionmentioning
confidence: 99%